Educational Intervention to Improve Knowledge and Attitudes about Thalassemia Premarital Screening Surveys among Muslim Societies: A Pilot Study in Indonesia - Rujito, Lantip; Pusparini, Indah; Lestari, Dyah Woro Dwi; Mulyanto, Joko (Fakultas Ilmu-ilmu Kesehatan, 2023)
Premarital screening is an effective preventive intervention to decrease the prevalence of thalassemia. However, the use of premarital screening is still low in Indonesia. This study assesses the effect of educational interventions on the knowledge and attitudes of Muslim couples regarding premarital screening for thalassemia in Indonesia. This pilot study used a pre-posttest design that included 17 premarital couples in Banyumas District. The participant’s knowledge and attitude regarding premarital screening for thalassemia were measured using a paper-based questionnaire before and after the intervention. The participants received a class-based lecture about thalassemia screening and were provided a handbook containing lecture material to read at home. The knowledge and attitude score was analyzed using Wilcoxon and Kruskal-Wallis test. The knowledge score significantly increased after the intervention, but the proportion of positive attitudes did not differ significantly. The participants knew that premarital screening for thalassemia was necessary; however, it did not affect their marriage decision. Thus, educational intervention increases the knowledge and shapes the attitude of couples toward thalassemia premarital screening but is inadequate for changing their behavior. Further exploration of the factors that affect the behavior of couples is needed to increase the use of premarital screening among couples in Indonesia.